Insights into the UDP-sugar selectivities of human UDP-glycosyltransferases (UGT): a molecular modeling perspective. (3rd July 2015) - Nair, Pramod C.; Meech, Robyn; Mackenzie, Peter I.; McKinnon, Ross A.; Miners, John O.
Abstract: Enzymes of the human uridine diphosphate (UDP)-glycosyltransferase (UGT) superfamily typically catalyze the covalent addition of a sugar from UDP-sugar cofactors to relatively small lipophilic compounds. The sugar conjugates are often biologically less active with improved water-solubility, facilitating more effective elimination from the body. Experimental data indicate that UGT proteins exhibit differing selectivities toward various UDP-sugars. Although, three-dimensional (3D) structures of UGT proteins are required to provide insights into the UDP-sugar selectivities observed for the various UGT proteins, there are currently, no experimental structures available for human UGTs bound to UDP-sugar(s). Thus, the absence of 3D structures poses a major challenge for analyzing UDP-sugar selectivity at an atomic level. In this commentary, we highlight the application of comparative homology modeling for understanding the UDP-sugar selectivities of UGT proteins. Homology models of the C-terminal (CT) domain indicate a highly conserved structural fold across the UGT family with backbone root mean-squared deviations (rmsds) between 0.066 and 0.079 Å with respect to the UGT2B7-CT X-ray crystal structure. The models show that four residues in the terminal portion of the CT signature sequence play an important role in UDP-sugar selectivity. The N-terminal domain is less likely to be associated with UDP-sugar selectivity, although, a conserved residue, Arg-259 (UGT2B7 numbering) in the UGT 1 and 2 families may influence UDP-sugar selectivity. Overall, the models demonstrate excellent agreement with experimental observations in predicting the key residues that influence the selectivity of UDP-sugar binding.